Rutin and Moringa oleifera leaf extract prevent monosodium glutamate-induced testicular toxicity in adult male albino rats - Abdel-Aty, Doaa M.; Ibrahim, Mona A.; Mohamed, Sherif R.; El-Khadragy, Manal F.; Abdel Moneim, Ahmed E.; Fathalla, Ayah S.; Soliman, Doaa (Frontiers in Veterinary Science, 2025)
IntroductionMonosodium glutamate (MG) is a substance often used to enhance food flavor, but its effect on the reproductive system is known to have a negative impact. This study assessed the protective effects of rutin (RUT) and Moringa oleifera leaf extract (MOLE) on testicular toxicity induced by MG in rats.MethodsThere were six groups: Control, RUT, MOLE, MG, RUT + MG, and MOLE + MG. The critical parameters measured were testicular index, hormone levels, antioxidants, oxidative stress markers, inflammation, apoptosis and histopathological changes.ResultsFollowing MG exposure (60 mg/kg/day for 30 days), the testicular index and serum testosterone, LH, and FSH levels were significantly reduced. The markers of oxidative stress increased, whereas the antioxidants decreased. The levels of inflammatory and apoptotic markers increased. The increased expression of inflammatory and apoptotic markers and significant testicular tissue damage, including degenerative changes in the seminiferous tubules, infiltration of inflammatory cells, and deposition of collagen fibers were investigated in addition to an increase in inflammatory and apoptotic markers.DiscussionThe present study showed that pre-administration of RUT or MOLE ameliorated the deleterious effects of MG, possibly due to antioxidant and anti-inflammatory properties, indicating a protective effect of RUT and MOLE on MG-induced testicular toxicity.